VALUE PERCEPTIONS OF PRACTICES AT A HUMAN MILK BANK - Tuâny Figueiredo Marinho; Valdecyr Herdy Alves; Maria Bertilla Lutterbach Riker Branco; Diego Pereira Rodrigues; Rosângela de Mattos Pereira; Giovanna Rosario Soanno Marchiori (Universidade Federal do Paraná, 2017)
This study was aimed at identifying and analyzing the value perceptions of health professionals working at the Human Milk Bank about their practices. A descriptive and qualitative study was undertaken. The participants were 24 health professionals working at a Human Milk Bank in the state of Rio de Janeiro. The data were collected between July 2012 and February 2013 through semistructured interviews. In the thematic content analysis of the testimonies, three categories emerged: The practice of guiding breastfeeding; Human milk donation, pasteurization and distribution: nutritional care; and Affection in breastfeeding as a facilitator of the mother-child bond. The interviewed professionals demonstrate satisfaction with their work and with the engagement in all activities relevant to the Human Milk Bank.